2006
DOI: 10.1158/1541-7786.mcr-06-0077
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Mitogen-Activated Protein Kinase Signaling Pathway in the Regulation of Human Melanocytic Antigen Expression

Abstract: Heterogeneous expression of melanocytic antigens occurs frequently in melanomas and represents a potent barrier to immunotherapy. We previously showed that coordinated losses of several melanocytic antigens are generally attributable to down-regulation of antigen gene expression rather than irreversible mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(130 citation statements)
references
References 59 publications
7
121
0
Order By: Relevance
“…3). These results are consistent with other work implicating MITF in melanoma survival (Haq et al 2013) 754 Genome Research www.genome.org therefore regulates two contrary effects of BRAF inhibition, namely, induction of melanocyte differentiation, which is an anti-tumorigenic effect important for immune cell recognition of melanoma (Kono et al 2006;Boni et al 2010;Liu et al 2013), and the pro-tumorigenic effect of engaging innate drug resistance to BRAF inhibition.…”
Section: Resultssupporting
confidence: 90%
“…3). These results are consistent with other work implicating MITF in melanoma survival (Haq et al 2013) 754 Genome Research www.genome.org therefore regulates two contrary effects of BRAF inhibition, namely, induction of melanocyte differentiation, which is an anti-tumorigenic effect important for immune cell recognition of melanoma (Kono et al 2006;Boni et al 2010;Liu et al 2013), and the pro-tumorigenic effect of engaging innate drug resistance to BRAF inhibition.…”
Section: Resultssupporting
confidence: 90%
“…39 In vitro, these inhibitors consistently enhance MLANA or SILV transcript levels, as reported for 70% of the melanoma cell lines treated with the ERK inhibitors PD98059 and U0126. 40 We found that in the LB2259-MEL human melanoma cells, the repressive effect of IL-1b on MITF-M expression was dependent on both NF-jB and JNK activation. MITF-M downregulation induced by IL1b was not mediated by ERK activation, because we found that inhibitors PD98059 and U0126 did not counteract this effect (data not shown).…”
Section: Tumor Immunologymentioning
confidence: 73%
“…Microphthalmia transcription factor-M (MITF-M), a melanocyte-specific master transcription factor, may also regulate MART-1 expression. 29,30 Reduced expression of MITF-M is associated with lack of MART-1 expression by melanoma cells. In our study, a melanoma that was negative for MART-1 and TRP-2 by IHC had evidence of MART-1 mRNA and TRP-2 mRNA in melanoma cells at the dermo-epidermal junction and in the superficial papillary dermis, but not in the deep dermis.…”
Section: Discussionmentioning
confidence: 99%